Stalemate - Llavore, Ma. Tara Mae Sampayan (2013)
"Stalemate showed the difficulty of choosing between other's expectations and what a person wants for himself. It explored the difference between what other's want for them and what they want. Other often have their own set of expectations towards a person thinking that it is best for that person. Their expectations are often pushed towards the person which then eventually becomes the normal thing for the person. At the same time, the person has their own wants and desires for themselves and these often makes them happier than what others want for them. These, more often than not, are hidden from others because it somehow doesn't match the expectations and because of this, it results into a discomfort and the need to choose between the two. The core of the film is based on Gender Theory and the dictation of femininity and masculinity in result, confines one's actions and decisions."